The influence of tourism seasonality on family business in peripheral regions - Lima, Gustavo Neves (2018)
In this conceptual article we explore the influence of tourism seasonality on family business in peripheral regions. We begin by reviewing the main characteristics of family business in peripheral regions. We proceed by reviewing literature on tourism seasonality as well as mitigation strategies at the macro level of analysis. As a corollary of such a literature review, we suggest a framework of strategies by which family businesses in peripheral regions may mitigate tourism seasonality. In particular, we combine an existing typology of coping, combating, and capitulating strategies with family business responses and service operations. We conclude by discussing the theoretical and practical implications of the framework.